Amomum tsao-ko Crevost et Lemarie extract targets the gut-liver axis to combat atherosclerosis in ApoE−/− mice - Wang, Qianqian; Niu, Yuanyuan; Huang, Jiawei; Huang, Junhong; Zhang, Jiamin; Zhang, Boyi; Guo, Zixuan; Feng, Shuying (Frontiers in Microbiology, 2025)
BackgroundAmomum tsao-ko Crevost et Lemarie (T-K), a valuable dual-purpose plant used in both medicine and food, exhibits a wide array of bioactivities and pharmacological effects, including the regulation of gastrointestinal function, promotion of weight loss and fat reduction, lowering of blood sugar levels, antioxidant activity. The efficacy of T-K and its underlying mechanism in managing atherosclerosis have rarely been discussed in the literature. This research aimed to evaluate the therapeutic potential of T-K in atherosclerotic mouse models induced by a high-fat high-cholesterol (HFHC) diet and to explore the potential mechanisms involved.MethodsAtherosclerotic mice were fed with an HFHC diet for 12 weeks, followed by a continuous oral administration of T-K extract via gavage for an additional 8 weeks. Full-length aorta Oil Red O staining, aortic root Oil Red O staining, and hematoxylin–eosin staining of liver tissues were employed to assess the efficacy of T-K. Biochemical methods and enzyme-linked immunosorbent assays were utilized to quantify alterations in inflammatory markers and oxidative stress indicators in serum and liver tissues. 16S rRNA sequencing technology was used to analyze alterations in the composition of the intestinal microbiota in animals following treatment with T-K.ResultsFull-length aorta Oil Red O staining, aortic root Oil Red O staining, and liver hematoxylin–eosin staining effectively evaluated the therapeutic potential of T-K in managing atherosclerosis. Serological tests confirmed T-K’s ability to decrease the total serum cholesterol and low-density lipoprotein cholesterol levels. Additionally, gut microbiota showed significant alterations following T-K treatment, which were markedly different from the changes observed after statin therapies. Furthermore, the results from the enzyme-linked immunosorbent assay indicated that T-K significantly reduced inflammation in both the aorta and liver. Oxidative stress assessments revealed that T-K can mitigate oxidative stress and thus improve atherosclerosis.ConclusionT-K has demonstrated significant efficacy in the treatment of atherosclerosis, primarily by lowering serum cholesterol levels and modulating intestinal flora at multiple levels to enhance disease management. Moreover, T-K mitigated the disease progression by attenuating oxidative stress and inflammatory responses in both the liver and aorta.